Evaluation of Carbon Nanoparticle Suspension and Methylene Blue Localization for Preoperative Localization of Nonpalpable Breast Lesions: A Comparative Study - Zhou, Yeqing; Liang, Yiran; Zhang, Jianshu; Feng, Yang; Li, Xiaoyan; Kong, Xiaoli; Ma, Tingting; Jiang, Liyu; Yang, Qifeng (Frontiers in Surgery, 2021)
Background：The resection of nonpalpable breast lesions (NPBL) largely depends on the preoperative localization technology. Although several techniques have been used for the guidance of NPBL resection, more comfortable and effective methods are needed. This aim of this study was to evaluate the use and feasibility of carbon nanoparticle suspension and methylene blue-guided resection of NPBL, to introduce alternative techniques. Methods：A total of 105 patients with172 nonpalpable breast lesions detected by breast ultrasound were randomized to carbon nanoparticle suspension localization (CNSL) group and methylene blue localization (MBL) group. The injection times of the two groups were divided into 2hrs, 4hrs, 6hrs, 12hrs, 16hrs and 20hrs before surgery. In the study, localization time, stained area, operation time, total resection volume (TRV), calculate resection ratio (CRR) and pathological diagnosis were assessed. Results：All of the 172 lesions were finally confirmed benign. Dye persisted in all cases in CNSL group (109/109, 100%), while only 53 cases in the MBL group (53/63, 84.1%) (P < 0.001). There was a significant correlation between dyeing time and dyeing area in MBL group (r = -0.767, P < 0.001), however, no significant correlation in CNSL group (r = -0.154, P = 0.110). The operation time were 11.05 ± 3.40 min in CNSL group and 13.48 ± 6.22 min in MBL group（P < 0.001）. The TRV were 2.51 ± 2.42 cm³ in CNSL group and 3.69 ± 3.24 cm³ in MBL group（P = 0.016). For CRR, CNSL group was lower than MBL group (7.62 ± 0.49 vs 21.93 ± 78.00, P = 0.018). There is no dye remained on the skin in the MBL group, however, dye persisted in 12 patients（19.4%）in CNSL group ( P = 0.001). Conclusion：CNSL and MBL are technically applicable and clinically acceptable procedures for intraoperatively localizing NPBL. Moreover, given the advantages of CNSL compared to MBL, including the ability to perform this technique five days before operation and smaller resection volume, it seems to be a more attractive alternative to be used in intraoperative localization of NPBL.